2013
DOI: 10.1175/jas-d-11-0338.1
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Modeling of Typhoon Morakot (2009): Vortex Rossby Waves and Their Role in Extreme Precipitation over Taiwan

Abstract: A high-resolution nonhydrostatic numerical model, the Advanced Regional Prediction System (ARPS), was used to simulate Typhoon Morakot (2009) as it made landfall over Taiwan, producing record rainfall totals. In particular, the mesoscale structure of the typhoon was investigated, emphasizing its associated deep convection, the development of inner rainbands near the center, and the resultant intense rainfall over western Taiwan.Simulations at 15-and 3-km grid spacing revealed that, following the decay of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…A prominent feature of VRWs is their spiral shape resulting from strong tangential wind shearing effect (Wang, ). The existence of VRWs in TCs has been confirmed by observational analysis (e.g., Corbosiero et al, ; Reasor et al, ) and numerical simulations (e.g., Chen & Yau, ; Franklin et al, ; Hall et al, ; Wang, , , ). VRWs are often coupled with convection and can affect TC intensity and the geometry of the eyewall (Chen & Yau, ; Nikitina & Campbell, ; Wang, ).…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…A prominent feature of VRWs is their spiral shape resulting from strong tangential wind shearing effect (Wang, ). The existence of VRWs in TCs has been confirmed by observational analysis (e.g., Corbosiero et al, ; Reasor et al, ) and numerical simulations (e.g., Chen & Yau, ; Franklin et al, ; Hall et al, ; Wang, , , ). VRWs are often coupled with convection and can affect TC intensity and the geometry of the eyewall (Chen & Yau, ; Nikitina & Campbell, ; Wang, ).…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, the coupling between the PV band and vertical velocity band indicates a strong feedback between the dynamics and thermodynamic factors (e.g., Chen & Yau, ; Hall et al, ; Wang, , ; Yu & Chen, ), as suggested by L18. Specifically, the positive perturbation of the PV wave first triggered convection via Ekman pumping.…”
Section: Mechanisms For the Rainband Formation And Maintenancementioning
confidence: 97%
See 2 more Smart Citations
“…Typhoon Morakot in Taiwan in August 2009 [1][2][3], severe floods in Pakistan in 2010 [4] and in Beijing in July 2012 [5,6], and Hurricane Sandy [7] in northeast U.S. in October 2012 have shown that the precipitation system tends to develop into heavier storms with a longer dry period between two precipitation events [8]. On 21 July 2012, a 60-year return period extreme storm hit Beijing and adjacent regions, triggering flash floods in the urban area and landslides in the mountainous region.…”
Section: Introductionmentioning
confidence: 99%